Pemikiran Pendidikan Islam Syekh Ahmad al-Qushashi dan Relevansinya di Era Modern - Hanif Fathoni (Fakultas Agama Islam, Universitas Hasyim Asy'ari, 2022)
Islamic education of Indonesia cannot be separated from the role of previous middle eastern scholars. Sheikh Ahmad al-Qushāshī is one of the middle eastern scholars who influenced previously the thinking of Indonesian scholars, whose students took many roles in Indonesian history. Some of the problems discussed in this study are the objectives, methods, educational curriculum and patterns of teacher-student interaction according to Sheikh Ahmad al-Qushāshī and their relevance to modern education in Indonesia. This research is a library research with analytical descriptive method, with several literature sources examined such as as-Simth al-Majid, Manżūmah al-Tawhīd, and other sources. The data analysis technique used is content analysis initiated by Shelley and Krippendorff. The results of research on the educational thinking of al-Qushāsh are briefly as follows: the purpose of education according to al-Qushāsh is to unite God, and become a pious servant. The educational curriculum is a curriculum based on monotheism which is divided into common, special and very special. The al-Qushāshī curriculum approach has an integration pattern between exoteric and esoteric sciences. The method of al-Qushāshī education is the exemplary method, bai'at-talqīn, al-Ŝuhbah and al-ta'dīb, taslīm, and Ilbās. The pattern of teacher-student interaction has a familial pattern of interaction (teachers act as parents, educators, and student guides), so that his thoughts are quite relevant to the modern era.